Mechanochemical synthesis of ZnS for fabrication of transparent ceramics - Ahn, Hak-Young; Choi, Won Jun; Lee, Seung Yong; Ju, Byeong-Kwon; Cho, So-Hye (SPRINGER, 2018)
Most radiation from the human body belongs to the long-wavelength infrared region (mainly at wavelengths of 10-12 mu m), which allows infrared (IR) sensors to distinguish humans or animals in the dark. One of the important components of such IR sensors is the IR window, which requires high transparency in the infrared region. ZnS is a most desirable substance for such windows due to its high transparency and high thermal stability. Herein, we report a low-cost environmentally friendly synthesis method for ZnS powder and its sintering for use as window material. Using only elemental precursors, Zn and S, submicrometer-sized ZnS powder with high phase purity was obtained. Spark plasma sintering was applied to compact the ZnS powder, and the resulting ceramic was analyzed by scanning electron microscopy, Fourier-transform infrared spectroscopy, Raman spectroscopy, and X-ray diffraction. We also examined the effect of an additive during sintering and found that LiF functions well as a sintering aid for the ZnS compact.
Keywords: PLASMA SINTERING SPS; OPTICAL-PROPERTIES; NANOPARTICLES; MICROSTRUCTURE; NANOCRYSTALS; NANOPOWDERS; TRANSITION; MORPHOLOGY; FACILE